Geophysical Characterization of Serpentinite Hosted Hydrogeology at the McLaughlin Natural Reserve, Coast Range Ophiolite. (19th January 2018) - Ortiz, Estefania; Tominaga, Masako; Cardace, Dawn; Schrenk, Matthew O.; Hoehler, Tori M.; Kubo, Michael D.; Rucker, Dale F.
Abstract: Geophysical remote sensing both on land and at sea has emerged as a powerful approach to characterize in situ water‐rock interaction processes in time and space. We conducted 2‐D Electrical Resistivity Tomography (ERT) surveys to investigate in situ hydrogeological architecture within the Jurassic age tectonic mélange portion of the Coast Range Ophiolite Microbial Observatory (CROMO) during wet and dry seasons, where water‐rock interactive processes are thought to facilitate a subsurface biosphere. Integrating survey tracks traversing two previously drilled wells, QV1, 1 and CSW1, 1 at the CROMO site with wireline and core data, and the Serpentine Valley site, we successfully documented changes in hydrogeologic properties in the CROMO formation, i.e., lateral and vertical distribution of conductive zones and their temporal behavior that are dependent upon seasonal hydrology. Based on the core‐log‐ERT integration, we propose a hydrogeological architectural model, in which the formation is composed of three distinct aquifer systems: perched serpentinite aquifer without seasonal dependency (shallow system), well‐cemented serpentine confining beds with seasonal dependency (intermediate system), serpentinite aquifer (deep system), and the ultramafic basement that acts as a quasi‐aquiclude (below the deep system). The stunning contrast between the seasonality in the surface water availability and groundwater storativity in the formation allowed us to locate zones where serpentinite weathering and possibly deeper serpentinization processes might have taken place. We based our findings primarily on lithological composition and the distribution of the conductive formation, our work highlights the link between serpentinite weathering processes and possible sources of water in time and space. Key Points: Seasonal variation of hydrogeology Serpentine aquifer Electrical Resistivity Tomography (ERT)